Microbial prevalence and outcome of diabetic foot ulcers in patient’s candidates for minor surgical interventions - Rafiq, Sangar Mohammed; Barawi, Omer Ali Rafiq; Jaff, Hamid Ahmed Mahmood; Hawez, Dahat Jamal (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Diabetes mellitus is a progressive disease with chronic complications such as diabetic foot infection, a significant difficulty that inevitably leads to gangrene and amputations. Objective: This study aims to determine microbial prevalence in diabetic foot infections, identify the significance of aggressive surgical therapy and minor amputations in limb salvage and the prevention of more proximal amputations, and identify predicting factors affecting the outcome of these surgical processes. Methods: In this cohort study, microbiological samples were collected from 62 patients with diabetic foot lesions who underwent debridement or minor amputations to determine the prevalence of microorganisms in diabetic foot infections. Then, they were followed up to determine the rate of saved limbs and the factors that affect the outcomes and rate of complications. Results: infections were mainly caused by aerobic Grampositive bacteria (S. aureus) 53.5%, and aerobic Gram-negative bacteria of enterobacter species 40.4%. Regarding the outcome of surgical intervention, we found an 80.65% success rate of saving the limb with a 30.6% complication rate. Risk factors such as high levels of inflammatory markers and parameters of the severity of peripheral arterial disease showed significant association with the rate of complications and poor outcomes. Conclusions: Debridement and minor surgical amputations effectively prevent more proximal amputations in diabetic foot infections with a high chance of good results. At the same time, the common microorganism in our local population was S. aureus, followed by P. mirabilis, E. coli, and Klebsiella species in diabetic foot infections.
Keywords: Diabetic foot infection; debridement; ray amputation; microbial prevalence